DIABETIC KIDNEY DISEASE: CURRENT APPROACHES TO DIAGNOSIS, PREVENTION AND THERAPY (1 part) - Borzykh, O.A. (World of Medicine and Biology, 2016)
The paper considers the issues associated with the early detection and timely diagnosis of diabetic kidney disease. Modern approaches to the diagnosis, the requirements of clinical guidelines and protocols to provide medical care for patients with diabetic kidney disease in the hospital and outpatient general practitioners and medical specialists (endocrinologist, cardiologist) have been covered.
Keywords: diabetic kidney disease; diagnosis; microalbuminuria; hyperfiltration